2008
DOI: 10.1016/j.imlet.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the anti-inflammatory properties of IL-27

Abstract: SummaryInitial studies on the biology of IL-27 provided evidence of a role for this cytokine in the initiation of Th1 responses; however, subsequent work using models of pathogen-induced and autoimmune inflammation have indicated that IL-27 has broad inhibitory effects on Th1, Th2 and Th17 subsets of T cells as well as the expansion of inducible regulatory T cells. While, the aim of this review is to highlight the functions of IL-27 in the context of inflammation it will also serve to elaborate on the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
168
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(184 citation statements)
references
References 88 publications
9
168
0
7
Order By: Relevance
“…In early studies, IL-27 was initially described as a proinflammatory cytokine that promoted Th1 responses (1,5). However, subsequent studies in multiple models of infectious and autoimmune diseases confirmed anti-inflammatory roles for IL-27 in Th1, Th2, and Th17 responses (6). Recent work showed that IL-27 can induce T cells to produce the anti-inflammatory cytokine IL-10 (7-9).…”
mentioning
confidence: 99%
“…In early studies, IL-27 was initially described as a proinflammatory cytokine that promoted Th1 responses (1,5). However, subsequent studies in multiple models of infectious and autoimmune diseases confirmed anti-inflammatory roles for IL-27 in Th1, Th2, and Th17 responses (6). Recent work showed that IL-27 can induce T cells to produce the anti-inflammatory cytokine IL-10 (7-9).…”
mentioning
confidence: 99%
“…Although IL-12 is critical for Th1 differentiation, IL-23 promotes the expansion and function of Th17 cells (1). IL-27 plays a complex role because it favors initial commitment into Th1 cells and the activation of CTLs in vivo; it also displays immunosuppressive properties (2,3). Initial research on IL-27 focused on its proinflammatory roles in the context of infection or cancer.…”
mentioning
confidence: 99%
“…However, recent studies have highlighted a predominant role of IL-27 as an anti-inflammatory agent that generates and maintains Treg functions, although inhibiting their in vivo reconstitution when present during the generation of Treg pool (20,21). Additionally, IL-27 induces IL-10 production by T lymphocytes (15,22) and reduces Th1, Th2, and Th17 responses (23). Although the large majority of studies were performed using murine cells, a similar divergent role of this cytokine has been recently described in human cells of both adaptive and innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WSX-1 2/2 mice develop lethal inflammation upon infection with a variety of pathogens (11,23,30,31). For instance, infection of these mice with Trypanosoma cruzi induces severe pathological changes owing to enhanced Th1 and Th2 cell responses, whereas infection with T. gondii causes uncontrolled tissue damage associated with exaggerated T cell responses mediated by activated Th1 cells and enhanced IL-17 production (11,31).…”
Section: Discussionmentioning
confidence: 99%